The role of geometry changes and debris formation associated with wear on the temperature field in fretting contacts - Jin, X.; Sun, Wei; Shipway, P.H. (Elsevier, 2016)
The temperature of a fretting contact is known to be a key factor in its development. However, as a test proceeds, the wear scar changes, both geometrically and through the formation of oxide-based debris-beds. Accordingly, the effects of these on the near-surface temperature field resulting from frictional heating in fretting has been analysed via numerical modelling. Under the test conditions examined, it was predicted that (i) the development of the wear scar geometry would result in a significant (up to ~ 25%) reduction in the mean-surface temperature rise, and (ii) the formation of a typical oxide debris bed would result in a significant (up to ~ 80%) increase in the mean-surface temperature rise.